Implementation of Independent Learning in Junior High Schools - Hanafiah Hanafiah; Dianti Yuniar; Titin Karlina (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this research is to find out the application of the independent learning curriculum in junior high schools, which explains the implementation of the independent learning curriculum in education units. This research using a qualitative research approach. The location of the research that the researcher will do is at SMP IT Fitrah Insani Garut. The instruments used in this study were interview guides, observation guidelines, and documentation studies. The results of this research reveal that SMP IT Fitrah Insani Garut has implemented independent learning through intra-curricular activities, projects to strengthen the profile of Pancasila students, and extracurriculars. At the planning stage all school stakeholders initiated by the Deputy Head of Curriculum Field compiled the things needed in learning, starting from learning tools, media and teacher readiness in carrying out learning for one academic year which will take place with the concept of the Independent Curriculum, At the implementation stage, implementing the curriculum This independence also has an impact felt by students, educators, and also other education personnel. In conclusion, SMP IT Fitrah Insani has prepared Merdeka Learning well and well planned